Incidence of hospitalization and its associated factors in first‐episode psychosis in Hong Kong. Issue 3 (19th February 2015) - Lee, Edwin H.M.; Hui, Christy L.M.; Lin, J.X.; Ching, Elaine Y.N.; Li, S.P.; Leung, W.G.; Chang, W.C.; Chan, Sherry K.W.; Chen, Eric Y.H.
Abstract: Aim: This study examined the incidence of hospitalization and its associated factors in patients with first‐episode psychosis in Hong Kong. Method: From 2009 to 2011, 360 patients were recruited consecutively as part of a controlled study of an early psychosis intervention service (the Jockey Club Early Psychosis project) in Hong Kong. Demographic and clinical information were obtained from face‐to‐face interviews and was reconfirmed using medical records. Factors relating to hospitalization during first episode were explored. Results: The incidence of hospitalization during first‐episode psychosis was 57.2%. Patients who were hospitalized had higher antipsychotics chlorpromazine equivalent dosage, higher positive and negative syndrome scale total score, higher Udvalg for Kliniske Undersøgelser others mean score and were more likely to have an acute mode of onset compared with those who were not hospitalized. Conclusions: Hospitalization was common in first‐episode psychosis. Future studies are needed to explore possible programmes to prevent hospitalization in patients with first‐episode psychosis.